Ethics and representation in feminist rhetorical inquiry - Dayton, Amy E.; Vaughn, Jennie (Pittsburgh series in composition, literacy, and culture., 2021)
"The historiography of feminist rhetorical research raises ethical questions about whose stories are told and how. Women and other marginalized people have been excluded historically from many formal institutions, and researchers in this field often turn to alternative archives to explore how women have used writing and rhetoric to participate in civic life, share their lived experiences, and effect change. Such methods may lead to innovation in documenting practices that took place in local, grassroots settings. The chapters in this volume present a frank conversation about the ways in which feminist scholars engage in the work of recovering hidden rhetorics, and grapple with the ethical challenges raised by this recovery work"--